Improving the Students Achievement in Speaking By Using Project-Based Learning Method - Humaimah Humaimah (Universitas Negeri Medan, 2012)
This study deals with the improvement of the vocational school students’ achievement through Project-Based Learning Method. This research was conducted by applying classroom action research in two cycles. The subject of this research was a class in the second year student of SMK TKJ HARAPAN STABAT. There were 35 students that participated in this research. The quantitative and the qualitative data were gathered by administering oral test and diary notes. The result of the quantitative data indicated that the score of the students improved from cycle I to cycle II with a pre-test mean of 59,5, the test of cycle I was 70, and the test of cycle II was 83,8. The result of the qualitative data indicated that the use of Project-Based Learning Method helped to improve the students’ achievement in speaking English. Key Words: Speaking, Project-Based Learning, Oral Test, Diary Notes